The role of interleukin 10 in human papilloma virus infection and progression to cervical carcinoma. (April 2017) - Berti, Fernanda Costa Brandão; Pereira, Ana Paula Lombardi; Cebinelli, Guilherme Cesar Martelossi; Trugilo, Kleber Paiva; Brajão de Oliveira, Karen
Graphical abstract: Highlights: Other factors than HPV exert influence on cervical carcinogenesis, including IL-10. IL-10 levels increase after HPV infection and as SIL progresses to cervical cancer. HPV proteins (E2, E6, E7) action over IL-10 gene leads to increased IL-10 levels, and IL-10 increases HPV E6 and E7 expression. An interplay between HPV and IL-10 creates a vicious cycle increasing IL-10 levels. Higher IL-10 levels allow viral persistence and favor cervical carcinogenesis. Abstract: Although Human Papillomavirus (HPV) exerts a vital influence on cervical carcinogenesis, other factors influence the development of a squamous intraepithelial lesion (SIL) that may or not progress to cervical cancer. Among several cytokines, Interleukin 10 (IL-10) stands out as an important anti-inflammatory factor, leading to immune system evasion through an immunosuppressive state. In the cervical microenvironment, during different stages of HPV infection, IL-10 production can be induced and maintained by different cell sources, including infected keratinocytes, some subsets of dendritic cells (DC), tumor associated macrophages (TAM), T regulatory cells (Treg) and tumor cells. Further, a wide range of effects can be exerted by IL-10 on different cell populations, such as inhibiting proinflammatory cytokine production, DCs differentiation, antigen presenting function and T-helper 1 (Th1) polarization. IL-10 is one of several cytokines involved in cancer development and sustenance, although its role in cancer is still controversial and poorly understood. However, cervical IL-10 levels tend to increase in parallel to SIL development and are even higher within cervical tumors. Accumulating data have shown that after HPV infection, IL-10 levels are enhanced as a result of HPV E2, E6 and E7 proteins action over IL-10 gene transcription, while IL-10 stimulates HPV E6 and E7 expression. Therefore, this interplay between HPV and IL-10 creates a vicious cycle that could favor an immunosuppressive microenvironment in the cervix, facilitating the progression of a simple HPV infection to SIL or cervical cancer.